Rancang Bangun Sistem Presensi Menggunakan Geolokasi Berbasis Aplikasi Android di PT. Milan Ecowood Indonesia - Tri Arvianto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The use of information technology in everyday life is unavoidable. In addition to facilitating human activities, information technology has become a corporate standard to support all of its business processes. One of the benefits of using information technology in a corporate environment is the use of an application for recording location-based attendance to record and become an administration system for employee attendance and absence. Currently, at PT Milan Ecowood Indonesia the available attendance system still uses fingerprint at the office location, this attendance system limits employees with salesperson positions which require employees to record their presence in the office area, so that time that should be used for working or lobbying candidates customers must be wasted during the trip to the office and then forwarded to the location of potential customers. The purpose of this research is to design and build an attendance system that can record data wherever employees are using geolocation based on an android application with the Flutter mobile application framework and using Google's Firebase DBMS. The final result of this research is the design of an attendance system using geolocation based on an android application that employees can use to make attendance wherever employees do their work.